Estudo de um leito fixo de pequena espessura utilizando CFD - Castro, Ubiranilson João de (Universidade Federal de São Carlos, 2016)
Studies carried out in fixed bed, a major experimental research equipment, use a simplified approach for assessing, for example, drying kinetics of various materials, known as thin-layer approach. For a given system can be encompassed in such an approach, the gas residence time in the system should be short enough so that it may be considered that the heat and mass balance between phases is quickly reached and moisture variation and temperature gas phase in the thin layer is negligible. However, some studies already show that structural parameters, the porosity, influence the speed profile of the behavior inside the bed, with a peak speed in the area close to the wall. Even with the advances in this field, obtaining measurements within the fixed bed are difficult to cause disturbances in its structure and changes in flow behavior, requiring the evaluation of the influence of the heat and mass transfer. Therefore, the analysis by techniques of Computational Fluid Dynamics (CFD) are shown as excellent usability for longer be applied in other similar complex systems that occur concurrent transfer mechanisms. In this context, the present study evaluated the drying process in a fixed bed of small thickness using the CFD technique (software ANSYS - FLUENT). For this study were tested with varying computational mesh refinement, analyzed results porosity distribution, air velocity, temperature and estimating the local mass transfer coefficient for the interior of a fixed bed dryer. The results show that should be used with caution thin layer approach because the energy available to the entire bed is not distributed uniformly, and the lower material layer receive more energy and get the greatest amount of heat in the gaseous phase in early stages of the dryer operation. The convective mass transfer coefficient indicates that the potential drying of such equipment varies as a function of position and time, mainly influenced by variations in system speed.
Keywords: Leito fixo; Cfd; Simulação; ENGENHARIAS::ENGENHARIA QUIMICA